2020
DOI: 10.14814/phy2.14420
|View full text |Cite
|
Sign up to set email alerts
|

Improved glucose tolerance with DPPIV inhibition requires β‐cell SENP1 amplification of glucose‐stimulated insulin secretion

Abstract: Pancreatic islet insulin secretion is amplified by both metabolic and receptor-mediated signaling pathways. The incretin-mimetic and DPPIV inhibitor anti-diabetic drugs increase insulin secretion, but in humans this can be variable both in vitro and in vivo. We examined the correlation of GLP-1 induced insulin secretion from human islets with key donor characteristics, glucose-responsiveness, and the ability of glucose to augment exocytosis in β-cells. No clear correlation was observed between several donor or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…At the very high concentration of 100 μM in G3, it showed the same effect in T2D than in ND islets during perifusions [ 186 ] but was 40% less effective during incubations [ 195 ]. Acutely, 100 nM glucagon-like peptide-1 (GLP-1) completely restored the responsiveness of T2D islets to glucose [ 188 ], but the effect was rather small at 10 nM [ 198 , 199 ]. One study compared the effects of GLP-1 and GIP in T2D islets and found the two incretins similarly effective in T2D islets, producing an increase in insulin secretion that was not different from that in ND islets [ 198 ].…”
Section: Dysfunctional Isletsmentioning
confidence: 99%
“…At the very high concentration of 100 μM in G3, it showed the same effect in T2D than in ND islets during perifusions [ 186 ] but was 40% less effective during incubations [ 195 ]. Acutely, 100 nM glucagon-like peptide-1 (GLP-1) completely restored the responsiveness of T2D islets to glucose [ 188 ], but the effect was rather small at 10 nM [ 198 , 199 ]. One study compared the effects of GLP-1 and GIP in T2D islets and found the two incretins similarly effective in T2D islets, producing an increase in insulin secretion that was not different from that in ND islets [ 198 ].…”
Section: Dysfunctional Isletsmentioning
confidence: 99%
“…The action of the incretins to facilitate insulin secretion is impaired in type 2 diabetes (T2D), although the underlying mechanism appears complex ( 3 ) and could involve altered receptor signaling ( 4 ). Incretin-induced insulin secretion from human islets correlates with the ability of glucose to augment depolarization-induced insulin exocytosis in single β-cells ( 5 ). In mice with impaired metabolism-insulin granule coupling, achieved by β-cell–specific deletion of the sentrin-specific protease 1 (SENP1), we showed that the β-cell response to the GLP-1 receptor agonist exendin-4 (Ex4) was impaired and that the ability of dipeptidyl peptidase 4 inhibition to improve oral glucose tolerance was greatly reduced ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pdx1-Cre mice (B6.FVB-Tg (Pdx1-cre)6 Tuv/J, Jackson Lab, 014647) on a C57BL/6 genetic background and Ins1-Cre mice on a mixed C57BL/6 and SV129 background 16 were crossed with Senp1-floxed mice on a C57BL/6 background 12 to generate gut/pancreas specific knockout mice (Pdx1-Cre + ;Senp1 fl/fl -pSENP1-KO) and β-cell specific knockout mice (Ins1-Cre + ;Senp1 fl/fl -βSENP1-KO) as described previously 7,12 . Pdx1-Cre + ;Senp1 +/fl mice (pSENP1-HET) and Ins1-Cre + ;Senp1 +/fl mice (βSENP1-HET) were used as heterozygotes, respectively.…”
Section: Animals and Dietsmentioning
confidence: 99%
“…The action of the incretins to facilitate insulin secretion is impaired in type 2 diabetes (T2D), although the underlying mechanism for such a failure appears complex 5 and could involve altered incretin receptor signalling 6 . Our recent study showed that incretin-induced insulin secretion from human islets correlates with the ability of glucose to augment depolarization-induced insulin exocytosis in single b-cells 7 . In transgenic mice with impaired metabolism-insulin granule coupling, achieved by b-cell specific deletion of the sentrin-specific protease-1 (SENP1), the b-cell response to the GLP-1 receptor agonist Exendin4 (Ex4) was impaired and the ability of DPP4 inhibition to improve oral glucose tolerance was greatly reduced 7 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation